1996
DOI: 10.1063/1.361786
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of slow oxide trap concentration profiles in metal–oxide–semiconductor transistors using the charge pumping method

Abstract: The charge pumping technique is shown to be a very efficient method for studying the slow traps in the oxide of metal–oxide–semiconductor (MOS) transistors. The trap concentration is obtained by varying the gate pulse frequency, the other measurement parameters being kept constant. The concentrations measured on virgin devices are in agreement with those generally obtained on state-of-the-art MOS transistors using noise measurements. On virgin and stressed devices, they also agree with those measured using a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 9 publications
5
74
0
Order By: Relevance
“…In fact, more accurate r p (0) should be dependent on temperature involving the multi-phonon process [5,28]. This approximation is based on the well established reports from different research groups regarding the relation between defect depth in the oxide and the CP frequency in thick gate oxide [29][30][31]. Contrarily, Ryan et al [28] conclude that the relationship is more complex than that expected.…”
Section: Extraction Methods Of Border-trap Densitymentioning
confidence: 97%
See 1 more Smart Citation
“…In fact, more accurate r p (0) should be dependent on temperature involving the multi-phonon process [5,28]. This approximation is based on the well established reports from different research groups regarding the relation between defect depth in the oxide and the CP frequency in thick gate oxide [29][30][31]. Contrarily, Ryan et al [28] conclude that the relationship is more complex than that expected.…”
Section: Extraction Methods Of Border-trap Densitymentioning
confidence: 97%
“…They are obtained for capture cross sections of electrons and holes at the Si/SiO 2 interface r n (0) = 5 . 10 À15 and r p (0) = 10 À16 -cm 2 and m n = m p = 0.5m 0 (details are given in [29]). At f H (500 kHz), we have found that CP-signal, corresponding to fast traps, emanates not only from N it but also from defects located at approximately 5 Å within interfacial oxide layer, even if frequency is increased (for example 1 MHz corresponds to Z = 4.6 Å and 10 MHz to Z = 3.5 Å).…”
Section: Nbti-induced Border-trap Within Interfacial Sub-oxide Regionmentioning
confidence: 99%
“…Assuming that ⌬F͑K͒ is a step function at K m , where ⌬F͑K͒ = 0.5, the trap concentration profiles are obtained from K m and N t ͑K m ͒ as in Ref. 15 K m = ln͑c n,p ͑0͒t h,l /͓ln͑3͔͒͒…”
Section: A As-measured Si-sio 2 Interface Trap Profilesmentioning
confidence: 99%
“…For high-k device, the Q cp is strongly influenced by the border traps at high frequency and increases with decreasing charge-pumping (CP) frequency. Approximate depth profiles of border traps N bt (x) obtained by adopting the derivative dQ cp /dlog(f) [20] and the related physical parameters are shown in Fig. 4.…”
Section: Methodsmentioning
confidence: 99%